The Optimization of Sharia Financial Institutions as Agent of Sale for Sukuk Product - Trimulato, Trimulato; Ismawati, Ismawati (Universitas Ahmad Dahlan, 2021)
The purpose of this study is to determine the development of state Sukuk, and efforts to optimize sharia financial institutions as distribution agents for the sale of state Sukuk products. Type of research used is qualitative research, the data source used is secondary data. Data collection is used through data collection from Financial Services Authority (OJK). The data analysis technique used in this research is descriptive qualitative. Results showed development state Sukuk in 2019 had succeeded in reaching 100 percent of the planned, namely 258.275 trillion. The issuance of SBSN type of Sukuk Ritel (SR) growth in 2019 has increased by 46,07 percent. Marketing of Sukuk products through sharia financial institutions, to convince the public that the Sukuk products are sharia products that can be obtained by sharia financial institutions. Product marketing through sharia financial institutions will also further introduce the existence of sharia financial institutions and can improve services to the public.